Alfredo Clemente Pinto e suas contribuições para o ensino de língua portuguesa: um estudo historiográfico - Almeida, Miguél Eugenio (2007)
In ALFREDO CLEMENTE PINTO AND HIS CONTRIBUUTIONS TO THE TEACHING OF PORTUGUESE LANGUAGE: AN HISTORIOGRAPHIC STUDY, we work the conception of grammar, tongue, language and teaching in the pseudo etymological period of Portuguese, especially of Pedagogical Grammar, The Mother Language, by Alfredo Clemente Pinto. Therefore, the purpose of this research is to develop a historiographic study of author s works in question. Thus, we follow Koerner and Swigger s Linguistic Historiography, where they point out the base-procedures of the methodology in question, which are described this way: 1) Contextualization it points to the epoch conceptions of the different philosophical, political, economic, scientific and artistic currents which in one way or another influenced each other in the determined historical period and, especially, the linguistic ideation and the social environment in general. 2) Immanence it seeks to evidence the internal elements of the language. 3) Suitability from the previous methodological procedures it advances in the attempt to approach the historical occurrences and the modern theories of linguistics in order to establish continuity and discontinuity relationships. We basically divide the work of this research into topics denominated like these: I - Historiography applied to Clemente Pinto s Didactic Works. We present a general view of the models of the historical doing, and under the methodological aspect, we stress Koerner s Linguistic Historiography (1966). II - Historical moment of two Brazilian Grammarians. We point out the possible relationships which contextualize, in Clemente Pinto and Eduardo Carlos Pereira, by seeking to show in general their historic and social context and, especially to visualize the link of Clemente Pinto and Eduardo Carlos Pereira to their educational activity and their projection in the teaching of the native language by means of the use of their didactic works. III - Language, Grammar and C.P. s and E.C.P s Grammar works. In this topic we seek to present the following points: 1) philological aspect of the writing which is pertinent to the research corpus; 2) notional aspects on language and grammar, demonstrating C.P. s and E.C.P. s position; 3) C.P. s works; 4) E.C.P. work. IV - Confrontation between Grammar and Grammatical Notes in Selecta, by Clemente Pinto. In this topic we notice what Selecta points out in the footnotes about questions of prosody, orthoepy, spelling, lexicology and syntax; and, next, we confront the occurrences with the grammars The Mother Tongue: Second Course (C.P.) and Expositive Grammar: Elementary Course (E.C.P.). At the following stage we achieve temporal approach of the past moment of the grammars (C.P./ E.C.P.) to the present moment by using the Modern Portuguese Grammar (Bechara)